Fungi associated with anthracnose of mango (Mangifera indica L.) fruits and their pathogenic potentiality (Dhaka University Journal of Biological Sciences, 2018)
A total of ten fungal species were isolated from the anthracnose symptoms of three varieties of Mangifera indica L. viz., Himsagar, Langra and Amrapali. The isolated fungi were Alternaria alternata (Fr.) Keissler, Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Tiegh., Colletotrichum gloeosporioides (Penz.) Sacc., Fusarium semitectum Berk. & Rav., Papulaspora sp. Preuss., Penicillium sp. Link., Pestalotiopsis guepinii (Desm.) Stey. and Rhizopus stolonifer (Ehrenb.) Vull. Colletotrichum gloeosporioides showed the highest per cent (26.82) frequency in Himsagar whereas R. stolonifer showed the lowest (2.22). Pestalotiopsis guepinii showed the highest per cent (46.83) frequency in Langra whereas R. stolonifer showed the lowest (1.17). Colletotrichum gloeosporioides showed the highest per cent (38.67) frequency in Amrapali whereas Papulaspora sp. showed the lowest (4.00). Among the isolated fungi C. gloeosporioides, F. semitectum and P. guepinii were found to be pathogenic to three mango varieties. Association of Fusarium semitectum, Papulaspora sp. and Pestalotiopsis guepinii with mango is new record in Bangladesh.Dhaka Univ. J. Biol. Sci. 27(1): 93-100, 2018 (January)